Perceptual Learning of Dysarthric Speech: A Review of Experimental Studies - Borrie, Stephanie A. (2011)
PURPOSE: This review article provides a theoretical overview of the characteristics of perceptual learning, reviews perceptual learning studies that pertain to dysarthric populations, and identifies directions for future research that consider the application of perceptual learning to the management of dysarthria. METHOD: A critical review of the literature was conducted that summarized and synthesized previously published research in the area of perceptual learning with atypical speech. Literature related to perceptual learning of neurologically degraded speech was emphasized with the aim of identifying key directions for future research with this population. CONCLUSIONS: Familiarization with unfamiliar or ambiguous speech signals can facilitate perceptual learning of that same speech signal. There is a small but growing body of evidence that perceptual learning also occurs for listeners familiarized with dysarthric speech. Perceptual learning of the dysarthric signal is both theoretically and clinically significant. In order to establish the efficacy of exploiting perceptual learning paradigms for rehabilitative gain in dysarthria management, research is required to build on existing empirical evidence and develop a theoretical framework for learning to better recognize neurologically degraded speech.